Seeds 2 : - Leonard, Ann (The Feminist Press at the City University of New York, 1995)
Seeds 2 documents economically viable projects borne from women's own initiatives and solidarity in Ecuador, Ethiopia, India, Mozambique, Nepal, Sudan, Thailand, the United States, and Zambia. These projects illustrate both the potential for and the difficulties of translating the rhetoric of economic development into meaningful lives for women.